2011
DOI: 10.1159/000327353
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Catechol-O-Methyltransferase Gene and Delirium in the Elderly

Abstract: Background/Aims: Catechol-O-methyltransferase, encoded by the COMT gene, is one of the enzymes that degrade dopamine. The aim of this study was to investigate whether polymorphisms in the COMT gene were associated with delirium. Methods: Patients aged 65 years and older, acutely admitted to the medical department or to the surgical department following hip fracture, were included. rs4680, rs4818, and rs6269 were genotyped. Results: Delirious patients were older, and more frequently had preexisting functional o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The absence of an association between COMT and postoperative delirium is consistent with one other study that examined this relationship. 19 In the latter work, polymorphisms in three single nucleotide polymorphisms (SNPs) on the COMT gene (rs4680 [examined in the current study], rs4818, and rs6269) were not associated with the development of delirium in older adults admitted to a medical department or to a surgical department post hip fracture. 19 We focused on only one SNP given its primary association with cognitive and neuropsychological vulnerability, and did find a modestly lower risk of delirium among COMT warriors, but this did not achieve statistical significance.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The absence of an association between COMT and postoperative delirium is consistent with one other study that examined this relationship. 19 In the latter work, polymorphisms in three single nucleotide polymorphisms (SNPs) on the COMT gene (rs4680 [examined in the current study], rs4818, and rs6269) were not associated with the development of delirium in older adults admitted to a medical department or to a surgical department post hip fracture. 19 We focused on only one SNP given its primary association with cognitive and neuropsychological vulnerability, and did find a modestly lower risk of delirium among COMT warriors, but this did not achieve statistical significance.…”
Section: Discussionmentioning
confidence: 78%
“…These strengths distinguish our study from previous work on COMT and delirium. 19 Additional study strengths include our state-of-the-art measures of delirium and nearly complete capture of data on COMT genotype and CRP across the population (98%).…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations in executive function can result in delirium, which affects mainly attention, and dementia, which affects mainly memory. Although COMT does not appear to influence delirium directly [34], it modified the known association between C-reactive protein (CRP), an acute phase reactant, and postoperative delirium [35]. Aging also influences cognition and among a biracial cohort of elders, COMT was associated with rate of cognitive decline with the val-allele having a protective effect [24].…”
Section: Neurological Conditions Deliriummentioning
confidence: 96%
“…Perturbations in executive function can result in delirium which affects mainly attention, and dementia which affects mainly memory. Although COMT does not appear to directly influence delirium, it modified the known association between C-reactive protein (CRP), an acute phase reactant, and postoperative delirium [34,35] Functional pain disorders A recent meta-analyses of COMT and functional pain disorders found that the low-activity met-allele was associated with fibromyalgia. An earlier meta-analysis also found that the met-allele was associated with fibromyalgia and widespread chronic pain, but not migraine headache or chronic musculoskeletal pain conditions [36,37] Chronic fatigue syndrome Chronic fatigue syndrome patients were more likely to be homozygous for the met-allele compared with val-allele carriers [38,39] Pain COMT low-activity haplotypes were associated with greater sensitivity to nociceptive, but lower sensitivity to neuropathic pain.…”
Section: Deliriummentioning
confidence: 99%
“…Patients were excluded if they were unable to speak or understand Dutch or English. The institutional medical ethics committee approved the study [22].…”
Section: Patients and Proceduresmentioning
confidence: 99%